A Preface to T.S. Elliot - Tamplin, Roland (Longman, 1988)
Preface Books are a series of scholarly and critical studies of major writers intended for those needing modern and authoritative guidance of their work, in order to reach intelligent understanding and enjoyment of it. This work focuses on T.S. Eliot